Do ICP-MS based methods fulfill the EU monitoring requirements for the determination of elements in our environment?. Issue 12 (21st October 2015) - Tirez, Kristof; Vanhoof, Chris; Bronders, Jan; Seuntjens, Piet; Bleux, Nico; Berghmans, Patrick; De Brucker, Nicole; Vanhaecke, Frank
Abstract : Undoubtedly, the most important advance in the environmental regulatory monitoring of elements of the last decade is the widespread introduction of ICP-mass spectrometry (ICP-MS). Abstract : Undoubtedly, the most important advance in the environmental regulatory monitoring of elements of the last decade is the widespread introduction of ICP-mass spectrometry (ICP-MS) due to standards developed by the European Committee for Standardization. The versatility of ICP-MS units as a tool for the determination of major, minor and trace elements (Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, Hg, K, Mg, Mn, Mo, Na, Ni, P, Pb, Sb, Se, Sn, Ti, V and Zn) in surface water, groundwater, river sediment, topsoil, subsoil, fine particulates and atmospheric deposition is illustrated in this paper. Ranges of background concentrations for major, minor and trace elements obtained from a regional case study (Flanders, Belgium) are summarized for all of these environmental compartments and discussed in the context of a harmonized implementation of European regulatory monitoring requirements. The results were derived from monitoring programs in support of EU environmental quality directives and were based on a selection of (non-polluted) background locations. Because of the availability of ICP-MS instruments nowadays, it can be argued that the main hindrance for meeting the European environmental monitoring requirements is no longer the technical feasibility of analysis at these concentration levels, but rather (i) potential contamination during sampling and analysis, (ii) too limited implementation of quality control programs, validating the routinely applied methods (including sampling and low level verification) and (iii) lack of harmonization in reporting of the chemical environmental status between the individual member states.